2022
DOI: 10.1038/s41419-022-04986-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CD44 signaling in leader cells induced by tumor-associated macrophages drives collective detachment in luminal breast carcinomas

Abstract: Collective detachment of cancer cells at the invading front could generate efficient metastatic spread. However, how cancer cell clusters shed from the leading front remains unknown. We previously reported that the dynamic expression of CD44 in breast cancers (BrCas) at collectively invading edges was associated with tumor-associated macrophages (TAMs). In this study, we first observed that the highly expressed CD44 (CD44high) cancer cell clusters were located in the BrCa circulating vessels, accompanied by CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…The elevated level of MSN in PI3K-activated MSC-derived CM was consistent with its tumor-suppressive actions on PANC1 and Pa03C pancreatic cancer cells. Immunoprecipitation supported MSN’s interaction with CD44, a non-kinase transmembrane glycoprotein 40 . CD44 is overexpressed in many types of cancer including pancreatic cancer 41 , and its high expression level in pancreatic cancer led to poor survival (p = 0.0045).…”
Section: Discussionmentioning
confidence: 86%
“…The elevated level of MSN in PI3K-activated MSC-derived CM was consistent with its tumor-suppressive actions on PANC1 and Pa03C pancreatic cancer cells. Immunoprecipitation supported MSN’s interaction with CD44, a non-kinase transmembrane glycoprotein 40 . CD44 is overexpressed in many types of cancer including pancreatic cancer 41 , and its high expression level in pancreatic cancer led to poor survival (p = 0.0045).…”
Section: Discussionmentioning
confidence: 86%
“…CD44 is a transmembrane glycoprotein that is a CSC marker in OSCC (Prince et al, 2007). Other studies have also demonstrated the presence of CD44 +ve cells at the edge of collective invasive masses (Gao et al, 2022, Wolf et al, 2020. For instance, showed that the invasive front of breast tumours exhibits a hybrid EMT phenotype, with high expression of CD44.…”
Section: Discussionmentioning
confidence: 98%